Sex-Specific Impact of Inflammation and Nutritional Indices on AVF Blood Flow and Maturation: A Retrospective Analysis - Özgür Akkaya; Ümit Arslan (Diagnostics)
Background: Arteriovenous fistula (AVF) failure rates are consistently higher in females, although the underlying mechanisms remain incompletely understood. Inflammatory processes play a key role in AVF remodeling and venous arterialization, yet their influence may differ by sex. This study aimed to evaluate the impact of inflammatory indices on AVF blood flow and maturation, with a focus on sex-specific differences. Methods: This retrospective analytical study included 110 patients (50 females, 60 males) undergoing initial surgical AVF creation. Postoperative assessments occurred at the fourth and sixth weeks. Patients demonstrating insufficient maturation (blood flow < 600 mL/min) at the fourth week were re-evaluated after two weeks without any intervening procedures or additional interventions. Results: Intraoperative Transit-Time Flow Measurement (TTFM) revealed significantly higher median AVF blood flow in males compared to females (289 mL/min vs. 200 mL/min; p < 0.001). Doppler ultrasonography (DUS) findings confirmed these sex-related differences, demonstrating consistently lower blood flow rates in female patients. An elevated neutrophil-to-lymphocyte ratio (NLR) was associated with approximately a 31% reduction in AVF blood flow among females, whereas an increased C-reactive protein-to-albumin ratio (CrA) correlated with an approximate 9% decline. In males, an elevated systemic immune-inflammation index (SII) and systemic inflammation response index (SIRI) were significantly associated with decreased AVF blood flow. Conversely, a higher prognostic nutritional index (PNI) positively correlated with AVF blood flow in both sexes. Risk factors associated with inadequate AVF maturation (<600 mL/min at sixth week) included female sex, advanced age, obesity, smoking, anemia, low vitamin D levels, and elevated inflammatory indices (NLR, SII, and SIRI). Conclusions: Inflammatory and nutritional indices derived from routine laboratory tests may assist in estimating AVF maturation likelihood. While DUS reliably assesses AVF blood flow, complementary evaluation methods may be required to assess the broader vascular status. Further research is needed to clarify sex-specific inflammatory mechanisms influencing AVF outcomes and to guide individualized management strategies.